1964
DOI: 10.2118/647-pa
|View full text |Cite
|
Sign up to set email alerts
|

Dead-End Pore Volume and Dispersion in Porous Media

Abstract: Experiments in 'wbr'cb calcium chloride displaced sodi~m chloride from four cores showed the extent of asymmetry in the resulting effluent concentration profiles.These results provided a check on bow validly the mixing process is modeled by a differential "(i.e., not finite-stage) capacitance matbernatical model. The effluent concentration profile from two consolidated cores exhibited corisidera ble asymmetry, while two unconsolidated cores yielded nearly symmetrical profiies. All runs resulted in brea~tbrough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
519
0
5

Year Published

1996
1996
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 988 publications
(558 citation statements)
references
References 0 publications
11
519
0
5
Order By: Relevance
“…1d) assumes that the soil micropore network is poorly connected and of such a low permeability that water is immobile in the vertical direction. The MIM approach was originally developed for simulation of fluid displacement in fractured petroleum reservoirs (Warren and Root, 1963;Coats and Smith, 1964). 2D or 3D (g.-j.…”
Section: Conceptual Modelsmentioning
confidence: 99%
“…1d) assumes that the soil micropore network is poorly connected and of such a low permeability that water is immobile in the vertical direction. The MIM approach was originally developed for simulation of fluid displacement in fractured petroleum reservoirs (Warren and Root, 1963;Coats and Smith, 1964). 2D or 3D (g.-j.…”
Section: Conceptual Modelsmentioning
confidence: 99%
“…If molecular diffusion drives lateral solute mixing, e.g., lateral mixing within a pore [Taylor, 1953] and diffusion into dead-end pores [Coats and Smith, 1964], the mixing time does not depend on the flow velocity, so that D• • v 2 [Passioura, 1971]. If lateral mixing is driven by advection rather than diffusion, the solute mixing time is inversely proportional to the average flow rate, t* = l*/v with l* a characteristic pore length [Skopp and Gardner, 1992].…”
Section: Definition Of Longitudinal Dispersivity •T L and Effective Fmentioning
confidence: 99%
“…The trust in these equations and corresponding parameter values was founded on the outcomes of laboratory studies with packed homogeneous soil columns in which the Darcy flow and Taylor dispersion (Taylor, 1953) describe the transport regime. Systematic deviations from the expected transport behavior in less homogeneous porous materials (Coats and Smith, 1964), in undisturbed soil columns (Kissel et al, 1973;Cassel et al, 1975;van Genuchten and Wierenga, 1977) and in field soils (Wild and Babiker, 1976) was the inducement for various refinements of the advectiondispersion equation. Field-scale solute transport experiments carried out during the last ten years have shown that the Richards-and the advection-dispersion equation may be valid in some cases and fail in many others (Jury and Flühler, 1992).…”
Section: Introductionmentioning
confidence: 96%